KESULITAN BELAJAR BALAGHAH MENGGUNAKAN KITAB MA'ANI KELAS XI SMA IT MIFTAHUL ALI LENDANG PENGKORES - Fathanah, Fani; Azzumar Fitri Bana, Rahil (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Balaghah studies play an important role in Islamic education by helping students understand the meaning and beauty of messages in the Qur’an and Hadith. However, its instruction at the secondary level faces challenges, especially when using classical texts like Ma’ani. This study aims to identify learning difficulties in Balaghah among 11th-grade students at SMA IT Miftahul Ali and to analyze teachers’ strategies in addressing them. A descriptive qualitative approach was applied using observation, interviews, and documentation, analyzed through the Miles & Huberman model. Results show that 70% of students struggle to comprehend classical Arabic sentence structures. Contributing factors include low motivation, limited vocabulary, and lack of environmental support. Effective strategies include problem-solving, individual approaches, visual media, and remedial instruction. These findings highlight the need for contextual and adaptive teaching methods and support the relevance of constructivist approaches in Arabic language education. ABSTRAK Kajian Balaghah memiliki peran penting dalam pendidikan Islam karena membantu memahami makna dan keindahan pesan Al-Qur’an serta Hadis. Namun, pembelajarannya di tingkat menengah menghadapi kendala, terutama saat menggunakan kitab klasik seperti Ma’ani. Penelitian ini bertujuan mengidentifikasi kesulitan belajar Balaghah pada siswa kelas XI SMA IT Miftahul Ali dan menganalisis strategi guru dalam mengatasinya. Pendekatan yang digunakan adalah kualitatif deskriptif dengan teknik observasi, wawancara, dan dokumentasi, serta dianalisis menggunakan model Miles & Huberman. Hasil menunjukkan 70% siswa mengalami kesulitan dalam memahami struktur kalimat Arab klasik. Faktor penyebabnya meliputi rendahnya motivasi, keterbatasan kosakata, dan dukungan lingkungan. Strategi efektif mencakup pendekatan problem solving, individu, media visual, dan remedial. Temuan ini menegaskan pentingnya strategi pembelajaran yang kontekstual dan adaptif, serta memperkuat relevansi pendekatan konstruktivisme dalam pembelajaran bahasa Arab.